Hubungan antara Minat dan Kebahagiaan menjadi Perajin Ukir Kayu Jepara - Adib Achmad Tasylichul (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
Since 2004-2015, there has been a decline in the number of Jepara woodcarvers. This phenomenon is allegedly caused by the lack of interest as woodcarvers. Ironically, those who are survive today, actually sell the carving at any price. The study about woodcarvers happiness was conducted to determine the effect of interest on happiness based on socioeconomic characteristics. The population of this study was all of the small-micro wood carving industries. The sampling was carried out using the stratified systematic sampling method with sample framework SE 2016 listing data. A total of 837 industry were allocated to 100 industry and were stratified into centers of 53 industries and non-centers of 47 industries. The analytical method used descriptive analysis and inferencing analysis. This study revealed that interest has a tendency to influence woodcarvers happiness, but the amount of income becomes its highest factor.